Peningkatan Daya Kinesik Sebagai Keterampilan Guru dalam Pembelajaran - Sumarta, I Wayan Ardi; Eko Rusminto, Nurlaksana; Pratama, Aditya (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
This community service program aims to improve teachers' skills in applying kinesic power strategies in learning. The main objective of this activity is to help teachers understand the concept of kinesic power, increase their insight into the use of nonverbal communication in teaching, and train them in applying kinesic power strategies effectively in the classroom. With this training, it is hoped that teachers can utilize body movements, facial expressions, and gestures optimally to improve interaction with students and clarify the delivery of learning materials. This training will apply various techniques for using kinesic power, where all participants can learn directly through practical experience so that the planned objectives can be achieved optimally. The methods used in this training include lectures, questions and answers, discussions, demonstrations, and direct practice.